The COVID-19 pandemic and food security in low- and middle-income countries: A review - Bloem, Jeffrey R.; Farris, Jarrad (Springer, 2022)
We review findings from the emerging microeconomic literature on observed changes in food insecurity associated with the COVID-19 pandemic. To do so, we focus our review on studies in low- and middle-income countries that include household survey data measuring food insecurity collected both before and after the onset of the COVID-19 pandemic. We first focus on several studies—seven from countries in Sub-Saharan Africa and one from India—that estimate immediate changes in food insecurity associated with the COVID-19 pandemic. Next, we review subsequent analysis studying longer term changes in food insecurity associated with the COVID-19 pandemic. This review, therefore, complements existing macroeconomic projections of food insecurity based on expected changes in income and prices.